Sequestration of dye from textile industry wastewater using agricultural waste products as adsorbents - Rangabhashiyam, S.; Anu, N.; Selvaraju, N. (Journal of environmental chemical engineering, 2013)
Agricultural wastes products are quite commonly distributed as the result of agricultural practices. They are inexpensive and subject to biodegradable. Agricultural waste is a good source for the adsorption of the dyes generated during the textile processing. For the process of adsorption, agricultural waste products are used as natural or in the modified form through activation process. This review article focuses on the various sources of the agricultural waste products and its adsorption capacity of the different dyes. Signifying the potential of the use of agricultural wastes products for removing off the toxic dye substances from the effluent discharging into the water bodies.